Experimental Single-Session Imagery Rescripting of Distressing Memories in Bowel/Bladder-Control Anxiety: A Case Series - Pajak, Rosanna; Kamboj, Sunjeev K. (Frontiers in Psychiatry, 2014)
Bowel and bladder obsession [bowel/bladder-control anxiety (BBCA)] is a viscerally centered phobic syndrome involving a specific concern about losing control of bowel or bladder functioning in a public place. Like other anxiety disorders, BBCA is characterized by intrusive imagery. We have previously described the nature of intrusive mental imagery in BBCA and found imagery themes to be linked to actual experiences of loss of control or to “near misses.” A causal role for imagery in symptom maintenance can be inferred by examining the effects of imagery rescripting. Moreover, successful rescripting may point to a potentially efficacious avenue for treatment development. Three cases of imagery rescripting are described here with pre-, post-, and follow-up (1-week) data reported. After rescripting, two participants experienced pronounced reductions in imagery vividness, distress, shame, disgust, and belief conviction. Most importantly, all three participants experienced a reduction in fear-associated bladder and/or bowel sensations. The results support a causal role for mental imagery in bowel-bladder-control anxiety and suggest that rescripting of distressing intrusive memories linked to recurrent images may be a useful avenue for development of cognitive-behavioral treatments of bladder/bowel-control anxiety.